The Evolution of The Senusian Movement and Its Principles in Libya - Elshbli, Adel A . Mohamed; Abdul Hamid, Faisal Ahmad Faisal (Journal Al-Muqaddimah, 2017)
The Senusian movement emerged in the middle of the nineteenth century in Libya and undertook the task of reforming and rebuilding the society. It started with a reformist religious call by its founder, Muhammad ibn Ali al-Sanussi, and al-Sanusiya founded the principles and principles of the movement. This study was based on the principles of the movement and its origin, as well as on the principles and origins of the Senusian movement, and we conclude that the movement Senussi to have succeeded politically, and socially and educationally succeeded in forming a cohesive society